2004
DOI: 10.1021/cm049786g
|View full text |Cite
|
Sign up to set email alerts
|

Organic Microelectronics:  Design, Synthesis, and Characterization of 6,12-Dimethylindolo[3,2-b]Carbazoles

Abstract: spectra were recorded on a Varian AS400 apparatus in appropriated deuterated solvent solution at 298 K. Chemical shifts were reported as δ values (ppm) relative to internal tetramethylsilane. Differential scanning calorimetry (DSC) was performed on Perkin-Elmer DSC7 module in conjunction with the Perkin-Elmer thermal analysis controller TAC7/DX at a heating rate of 2°C/min. UV-visible absorption spectra were recorded on a Hewlett-Packard diode-array spectrophotometer (model 8452A) using 1 cm path length quartz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
118
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 29 publications
2
118
0
Order By: Relevance
“…INC is known to show strong blue fluorescence under irradiation by ultraviolet (UV) light. In recent years, there have been some reports on the preparation and characterization of derivatives of INC. [16][17][18][19][20][21][22][23][24][25] In particular, Hu et al 21 have reported 1,7-dinaphtylindolo [3,2-b]carbazole, which showed excellent hole-transport properties in light-emitting diodes. Later, the first organic field-effect transistors using N-alkylated INC as an active layer was successfully fabricated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…INC is known to show strong blue fluorescence under irradiation by ultraviolet (UV) light. In recent years, there have been some reports on the preparation and characterization of derivatives of INC. [16][17][18][19][20][21][22][23][24][25] In particular, Hu et al 21 have reported 1,7-dinaphtylindolo [3,2-b]carbazole, which showed excellent hole-transport properties in light-emitting diodes. Later, the first organic field-effect transistors using N-alkylated INC as an active layer was successfully fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the first organic field-effect transistors using N-alkylated INC as an active layer was successfully fabricated. 16 In addition, there have also been some reports on polymers containing the INC moiety. [26][27][28][29] For example, Li et al 15 synthesized a new class of polyindolocarbazole via the coupling polymerization of 2,8-dichloroindolo [3,2-b]carbazole derivatives, a film of which could be manufactured by spin coating and exhibited a field-effect transistor mobility of 0.02 cm 2 V À1 s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Indolocarbazoles are currently investigated as materials for optical (Nemkovich et al, 2009) and electronic applications (Wakim et al, 2004;Zheng et al, 2015). Among the different synthetic routes (Vlasselaer & Dehaen, 2016), the twofold Cadogan reaction (Cadogan et al, 1965) is a very successful route to indolocarbazoles (Kistenmacher & Mü llen, 1992;Wrobel et al, 2013) and is also suitable for the preparation of higher oligomers (Srour et al, 2016).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Namely, materials based on them are very promising because of their great stability, good solubility, excellent photoconductive properties, relatively intense luminescence, and good performance in OFETs, OLEDs, and thermoelectric materials [42][43][44][45][46][47][48][49][50][51][52]. Moreover, these compounds, and particularly halogenated carbazoles, are important synthetic intermediates and pharmacological targets [53].…”
Section: Introductionmentioning
confidence: 99%